2014
DOI: 10.4103/0970-9290.138310
|View full text |Cite
|
Sign up to set email alerts
|

An epidemiological study to determine the prevalence and risk assessment of gingivitis in 5-, 12- and 15-year-old children of rural and urban area of Panchkula (Haryana)

Abstract: The results showed that the percentage of children affected with gingivitis was significantly higher in the rural areas in 5- and 15-year-old children, but this trend was not seen in 12-year age group, reflecting the lack of awareness in rural areas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
5
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 0 publications
3
5
1
2
Order By: Relevance
“…Changes in biofi lm composition during adolescent period of life can be explained with increase plaque accumulation due to improper oral hygiene. As soon as orthodontic appliances are bonded, plaque removal becomes more diffi cult to accomplish and moderate gingivitis can be detected in the early stage of this kind of treatment [7].…”
Section: Discussionmentioning
confidence: 99%
“…Changes in biofi lm composition during adolescent period of life can be explained with increase plaque accumulation due to improper oral hygiene. As soon as orthodontic appliances are bonded, plaque removal becomes more diffi cult to accomplish and moderate gingivitis can be detected in the early stage of this kind of treatment [7].…”
Section: Discussionmentioning
confidence: 99%
“…to better take care of the oral health of their children. Studies conducted in India the group of 5 years, and among other age groups, have shown more schoolchildren affected with gingivitis in rural areas than in urban areas [22,23]. Overall, except for "region" these results suggest a lack of social inequalities in the occurrence of gingivitis for studied variables.…”
Section: Prevalence Of Gingivitis and Associated Factorsmentioning
confidence: 48%
“…Many surveys have shown that gum disease was widespread among children. The prevalence of gingivitis was much higher and the severity increased more in many countries of Asia and Africa than in the US or the European countries [18][19][20][21][22][23], despite the methodological approaches that vary from one study to another, particularly in the operational definition of gingivitis. By sex, the rate of children with gingivitis was higher among boys (15.3%) than among girls (13.1%), but this difference was not significant (p = 0.38).…”
Section: Prevalence Of Gingivitis and Associated Factorsmentioning
confidence: 99%
“…Kaur A conducted a study amongst 12 years old children in Haryana, India. He concluded that the prevalence of gingivitis in the study group from the rural group is 94% 19 . The results are in accordance with our results, showing a high prevalence of gingivitis.…”
Section: Discussionmentioning
confidence: 97%